What role for national parliaments in EU governance? A view by members of parliament. Issue 6 (18th August 2021) - Kinski, Lucy
ABSTRACT: Scholars have written much about what national parliaments can, should and actually do in European Union (EU) governance. What they have largely disregarded so far is the actors' perspective. Which roles do national members of parliament (MPs) themselves view as a priority and how do they assess their performance? Which factors may structure observed variation? From a strategic perspective on legislative behavior, the article conceptualizes five roles for national MPs in EU politics: Scrutinizers, Subsidiarity Watchdogs, Networkers, Communicators and Transposers . It draws on plenary debates on the Constitutional Treaty, the Lisbon Treaty and the Eurozone crisis as well as data from 66 interviews with MPs from Austria, Germany, Ireland and the United Kingdom. There is a clear focus on scrutiny in EU affairs and communication to citizens. Ideological conviction and debate topics structure patterns in emphasis and assessment of these roles, while government-opposition dynamics and parliamentary strength only partially do.